Effets biologiques de Salviaofficinalis - Benmendas, Meriem; Mamoun, Karima (My University, 2017)
The present work aims to evaluate the antioxidant and anti-inflammatory effect of the ethanolic extract of Salvia officinalis (EES). The in vitro study involved determining the level of polyphenols and flavonoids in this extract, as well as the evaluation of its antioxidant properties (by the 2, 2-diphenyl-1-picrylhydrazyl or DPPH test). A total of 25 male rats weighing between 100 and 150 g were divided into five batches of five animals each and receiving EES (100 and 200 mg / kg), quercetin (50 mg / kg) or diclofenac (100 Mg / kg) orally for seven days to investigate the anti-inflammatory activity of EES in vivo. Induction of inflammation was made by intra-peritoneal injection of carrageenan. At the end of the experiment, the blood samples were taken by cardiac puncture and the peritoneum was recovered. Salvia officinalis contains 21.08 mg EAG / g and 0.54 mg EQ / mg, this extract showed a high rate of free radical scavenging (IC50 = 0.99 μg / mL). Biochemical analyzes showed a highly significant decrease in the level of PGE2, creatinine, urea, CRP, fibrinogen in rats treated with (200 mg / kg) EES and an increase in total protein albumin and transferrin, confirming That salvia officinalis has an anti-inflammatory effect. Sage helps to restore disturbances of homeostasis and carrageenan-induced inflammation markers in Wistar rats.
Keywords: Salvia officinalis; inflammation; Wistar rats; antioxidant activity; Salviaofficinalis; inflammation; les rats Wistar; activité antioxydante